A Hydrogen‐Bond‐Assisted CHEF Approach for Colorimetric and Fluorescence Recognition of Picric Acid and Its Solid‐Phase Extraction by an Immobilized Probe. Issue 22 (12th June 2018) - Ghosh, Milan; Ta, Sabyasachi; Banerjee, Mahuya; Mahiuddin, Md; Das, Debasis
Abstract: Two rhodamine derivatives derived from rhodamine B, salicyaldehyde (L) and benzaldehyde (R1) having ether spacer have been prepared and characterised by spectroscopic techniques. One of them (L) is very efficient to detect picric acid (PA) by colorimetric and fluorescence method while the other (R1) serves as model compound to unveil sensing mechanism. The probe (L) recognizes PA through hydrogen bond assisted Chelation Enhanced Fluorescence (CHEF) process in a ratiometric manner in aqueous‐methanol (4/1, v/v). The silica immobilised probe is suitable for highly efficient solid phase extractive removal of PA from environmental samples. The experimental results have been substantiated by DFT studies. Abstract : Salicylaldehyde appended rhodamine derivative having ether spacer efficiently detects picric acid (PA) both by colorimetric and fluorescence method. A model compound, devoid of phenol ‐OH group is prepared and studied to unveil the sensing mechanism. The probe recognizes PA through hydrogen bond assisted Chelation Enhanced Fluorescence (CHEF) process in a ratiometric manner in aqueous‐methanol (4/1, v/v). The immobilised probe is suitable for highly efficient solid phase extractive removal of PA from environmental samples. The experimental results have been substantiated by DFT studies.